ANALISIS ANALYSIS OF PANEL DATA OF POVERTY IN ACEH PROVINCE - Dewi Maya Sari; Zulfan (Puslatbang KHAN, 2021)
This study aims to analyze the effect of gross regional domestic product and village funds on poverty in Aceh Province. The data used are secondary data in the form of Gross Regional Domestic Product (PDRB) data, village fund transfer data and poverty data from 23 districts / cities in Aceh Province over a three-year period (2017 to 2019). This study uses panel data regression analysis where the model used is the common effect. The results of this study indicate that the Gross Regional Domestic Product (GRDP) and village funds has a positive effect on poverty.